Creating awareness of rabies in pupil of Z.P. High School in Kallur (V), Kurnool (Dist), Andhra Pradesh - Srigouri, Thalikota; Shridevi, Kotina (International Journal Of Community Medicine And Public Health, 2018)
Background: Rabies is a deadly disease but mostly preventable. Poor public awareness towards rabies is considered as one of the bottle necks for the prevention and control of the disease. The objectives of the study were to create awareness of rabies in pupil of Z.P. High School in Kallur (V), Kurnool (Dt) and to formulate Recommendation to school and concerned authorities Methods: A longitudinal intervention study conducted in Z.P. High school from a period of November 1st 2011 to December 31st 2011 among 6th to 9th class school children. And sample size was 160 students. A predesigned, semi structured questionnaire consisting of 28 questions was given to assess their level of awareness regarding rabies. Results: Of the 160 school children interviewed, 98 (61%) of them were males and 62 (38%) female students. The major source of information regarding occurrence of rabies 54 (33.7%) is schools, awareness regarding rabies due to dog bite before pre educational intervention is only 65 (40.62%), only 25% were aware of T.T vaccination, 41% were aware of anti-rabies vaccination. 59.3% were aware of cleaning of wound. Only 36 to 38% were aware of dog vaccination. Conclusions: In conclusion, this study has shown that the level KAP about clinical signs of rabies, prevention methods after suspected animal bite, the first action taken after rabid dog bite is not so good in the school, An intervention was planned in three sessions, and students were educated on how to identify rabid dogs, preventive measures like cleaning of wound after bite, dog vaccination, human vaccination with anti-rabies vaccine and T.T vaccine.